CONTRIBUTION OF FISHERMEN'S WIFE ON FISHERY PRODUCT PROCESSING TO HOUSEHOLD INCOME IN LUBUK PUDING SUB-DISTRICT, BURU DISTRICT, KARIMUN REGENCY, RIAU ISLANDS - Sakanah Sakanah; Kusai Kusai; Lamun Bathara (Berkala Perikanan Terubuk, 2021)
This research was carried out in February 2020 in Lubuk Puding Village, Buru District, KarimunRegency, Riau Islands Province. The purpose of this study was to determine the activities of fishermen'swives, to describe the use of time, and to find out the contribution of fishermen's wives in helping toimprove the economy of fishermen's households to reduce the burden of family dependents in LubukPuding Village, Buru District, Karimun Regency, Riau Islands Province. The method used is a surveymethod by selecting respondents through a census, namely fishing households have a working wife. Thenumber of respondents as many as 25 people.The results of this study indicate that the fisherman's wife's activities include activities that are not carriedout, namely processing salted fish, processing fish crackers, processing shrimp crackers, processingshrimp paste, processing dried shrimp and processing atomic crackers. The average working time forUndomestic activities is 16.04 hours/week. The contribution of fishermen's wives to the household incomeof fishermen who own nets is in the low category, which is 21.23%. The contribution of net fishermen'swives is in the medium category, which is 40.25%. The contribution of fishermen's wives who own trapsis in the very low category, namely 18.81%. The contribution of the fishermen's wife of bubu fishermen isin the low category, which is 21.51%.